2017
DOI: 10.1051/matecconf/201712601002
|View full text |Cite
|
Sign up to set email alerts
|

Quadcopter thrust optimization with ducted-propeller

Abstract: Abstract-In relation to quadcopter body frame model, propeller can be categorized into propeller with ducted and without ducted. This study present differences between those two using CFD (Computational Fluid Dynamics) method. Both categories utilize two blade-propeller with diameter of 406 (mm). Propeller rotation generates acceleration per time unit on the volume of air. Based on the behavior of generated air velocity, ducted propeller can be modeled into three versions. The generated thrust and performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
(7 reference statements)
0
2
0
3
Order By: Relevance
“…The additional weight of the shroud is a major disadvantage of shrouded rotor systems as the aerodynamic benefit is penalized by the additional thrust requirement to carry the shrouds. Kuantama et al [13] demonstrated the use of CFD to analyze shrouded and open rotor configurations. The study compared different shroud geometries with the aim to minimize the total weight of the shroud.…”
Section: Introductionmentioning
confidence: 99%
“…The additional weight of the shroud is a major disadvantage of shrouded rotor systems as the aerodynamic benefit is penalized by the additional thrust requirement to carry the shrouds. Kuantama et al [13] demonstrated the use of CFD to analyze shrouded and open rotor configurations. The study compared different shroud geometries with the aim to minimize the total weight of the shroud.…”
Section: Introductionmentioning
confidence: 99%
“…Di sisi lain, peningkatan kecepatan putaran propeler juga mampu meningkatkan thrust yang dihasilkan [11], [12]. Namun, perbedaan signifikan baru akan terlihat pada putaran propeler yang tinggi (di atas 4.000 rpm) [13].…”
Section: Analisis Thrustunclassified
“…Також проведено оцінку застосовуваних методів, результатів і основних параметрів, а також автори представляють свої міркування з проблематики майбутніх досліджень щодо досліджень квадрокоптерів. У роботі [9] проаналізовано переваги та недоліки квадрокоптерів з відкритими та закапотованими гвинтами з використанням методу CFD (Computational fluid dynamics). Об'єктом дослідження обрано дволопатевий гвинт діаметром 406 мм.…”
Section: вступunclassified